1999
DOI: 10.1023/a:1022350023163
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The HFFQ is a simple self-administered questionnaire completed by the child's parent or guardian and is useful in assessing the diets of Native American and Caucasian children. It may also provide important nutritional information about this age group for future program planning, research, education, and intervention purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
57
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(62 citation statements)
references
References 6 publications
5
57
0
Order By: Relevance
“…The correlation coefficients for most of the nutrients and foods groups were comparable with those observed in other validation studies of FFQ in children and young populations [10, 11, 3136]. In our study, reproducibility was assessed by comparing the results from the FFQ administered twice over a period of 9 months, while validity was examined by comparing the nutrient and food intakes from FFQ with the intakes from three 24hDR and several nutrient intakes in plasma (carotenoids, vitamins C, E and retinol).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The correlation coefficients for most of the nutrients and foods groups were comparable with those observed in other validation studies of FFQ in children and young populations [10, 11, 3136]. In our study, reproducibility was assessed by comparing the results from the FFQ administered twice over a period of 9 months, while validity was examined by comparing the nutrient and food intakes from FFQ with the intakes from three 24hDR and several nutrient intakes in plasma (carotenoids, vitamins C, E and retinol).…”
Section: Discussionsupporting
confidence: 85%
“…Nonetheless, the number of validity studies of FFQs to assess food and nutrient intakes in young children is much lower, probably as a result of the many dietary changes at these ages due to the rapid development and growth of the child [4]. In a systematic review of thirty-two articles by Ortiz-Andrellucchi on dietary assessment methods for micronutrient intake in infants, children and adolescent, eight studies presented validation data for FFQ in preschool children aged 2–5 years [8], although only two studies showed that past dietary intake of preschool children could be measured reasonably well when comparing their results with food records or dietary recalls [9, 10]. Only one study showed a good correlation for vitamin C and weak or no correlation for other micronutrients (vitamin D, retinol and b-carotene), when dietary intakes from FFQ were compared with plasma concentrations [11].…”
Section: Introductionmentioning
confidence: 99%
“…Parent and child sugary beverage intake was assessed using questions from food frequency questionnaires previously validated in a pediatric populating (Native American and Caucasian children ages 1–5 years) [38, 39]. Average daily sleep for both parent and child was measured by self-reported sleep and wake times (assessed separately for weekdays and weekends).…”
Section: Methods: Feasibility Trial Of Parents Working Together (Pwt)mentioning
confidence: 99%
“…Maternal education status was reported as high school, some college, and college or more. Dietary data was obtained from a validated food-frequency questionnaire administered at each visit that asked about consumption of various food items in the past 30 days [37]. Screen time was calculated from the reported number of hours spent watching television, playing video games, or using a computer on an average school day.…”
Section: Methodsmentioning
confidence: 99%